2010
DOI: 10.1093/sleep/33.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Sleep Duration and Insomnia and the Risk of Cardiovascular Events and All-cause Death: Report from a Community-Based Cohort

Abstract: Sleep duration and insomnia severity were associated with all-cause death and CVD events among ethnic Chinese in Taiwan. Our data indicate that an optimal sleep duration (7-8 h) predicted fewer deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
207
4
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(228 citation statements)
references
References 42 publications
13
207
4
4
Order By: Relevance
“…Spline analysis using linear models did not shown any difference in events with shorter duration than 7 hours for both cardiovascular mortality (8 studies)11, 25, 44, 47, 49, 71, 87, 88 and CVD (7 studies) 8, 12, 22, 33, 38, 42, 74. However, longer self‐reported sleep duration >7 hours appeared to be associated with a moderate increase in greater stroke mortality (cubic model shown in Data S8).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Spline analysis using linear models did not shown any difference in events with shorter duration than 7 hours for both cardiovascular mortality (8 studies)11, 25, 44, 47, 49, 71, 87, 88 and CVD (7 studies) 8, 12, 22, 33, 38, 42, 74. However, longer self‐reported sleep duration >7 hours appeared to be associated with a moderate increase in greater stroke mortality (cubic model shown in Data S8).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 74 studies met the inclusion criteria; the process of study selection is shown in Figure 1 8, 9, 11, 12, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89,...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inadequate sleep is common, with 28% of the US adult population reporting ≤6 hours of sleep per night and with that, a corresponding 24% increased risk of cardiovascular disease 1, 2, 3, 4, 5, 6, 7. Women adopt such behavior in disproportionately greater numbers in part because of lifelong demands on them as caregivers, first to their children and later to ailing and/or elderly family members 8, 9.…”
Section: Introductionmentioning
confidence: 99%